Genetic variation in VEGF does not contribute significantly to the risk of congenital cardiovascular malformation. - Griffin, H; Hall, D; Topf, A; Eden, J; Stuart, A; Parsons, J; Peart, I; Deanfield, J; O'Sullivan, J; Babu-Narayan, S; Gatzoulis, M; Bu'lock, F; et al. (Public Library of Science, 2009)
Several previous studies have investigated the role of common promoter variants in the vascular endothelial growth factor (VEGF) gene in causing congenital cardiovascular malformation (CVM). However, results have been discrepant between studies and no study to date has comprehensively characterised variation throughout the gene. We genotyped 771 CVM cases, of whom 595 had the outflow tract malformation Tetralogy of Fallot (TOF), and carried out TDT and case-control analyses using haplotype-tagging SNPs in VEGF. We carried out a meta-analysis of previous case-control or family-based studies that had typed VEGF promoter SNPs, which included an additional 570 CVM cases. To identify rare variants potentially causative of CVM, we carried out mutation screening in all VEGF exons and splice sites in 93 TOF cases. There was no significant effect of any VEGF haplotype-tagging SNP on the risk of CVM in our analyses of 771 probands. When the results of this and all previous studies were combined, there was no significant effect of the VEGF promoter SNPs rs699947 (OR 1.05 [95% CI 0.95-1.17]); rs1570360 (OR 1.17 [95% CI 0.99-1.26]); and rs2010963 (OR 1.04 [95% CI 0.93-1.16]) on the risk of CVM in 1341 cases. Mutation screening of 93 TOF cases revealed no VEGF coding sequence variants and no changes at splice consensus sequences. Genetic variation in VEGF appears to play a small role, if any, in outflow tract CVM susceptibility.